Concealed Penis after Circumcision: Is It Beneficial in Lowering Uropathogenic Colonization in Penile Skin and Preventing Recurrence of Febrile Urinary Tract Infections? - Özkidik, Mete; Telli, Onur; Hamidi, Nurullah; Bagci, Uygar; Hüseyinov, Adil; Kayis, Aytaç; Ibrahimov, Anar; Soygür, Tarkan; Burgu, Berk (Urology Journal, 2020)
Purpose: To discuss whether concealed penis after circumcision lowers perimeatal urethral and glanular sulcus uropathogenic bacterial colonization in healthy boys with no urinary tract problems and prevents attacks of febrile urinary tract infections in non-healthy boys with defined urinary tract abnormalities. Materials and Methods: This case-control study was conducted in Ibn-i Sina Hospital and retrospectively collected data of 471 boys were analyzed. All patients were scanned for any urinary tract abnormality and those with any defined abnormalities were classified as non-healthy group. (123 patients) Non-healthy patients were divided into two subgroups as concealed (n:31) and non-concealed (n:92) penis after circumcision. Healthy patients with no urinary problems were divided into three groups as circumcised without concealed penis (n:144), with concealed penis after circumcision (n:104) and uncircumcised control group (n:100). Bacterial cultures were obtained from both periurethral meatal and glanular sulcus areas by adhering strictly to the rules of obtaining bacterial culture to avoid false-positive or negative culture results. Also only uropathogenic bacterias were evaluated, irrelevant results were excluded. Results: Mean age was similar in healthy population. Comparison of three groups showed that there was a significant difference in both cultures.(P = .026 for periurethral meatal region, P = .039 for glanular sulcus region) In post hoc analysis, non-concealed group had a lower rate of culture positivity in both areas compared to other groups. Mean age was also similar in non-healthy population. Mean follow-up period was 18.2 months. Patients with concealed penis after circumcision had a significantly higher number of febrile UTI attacks (20 attacks in 8 patients vs 7 attacks in 5 patients) compared to non-concealed group. (P = .019) All febrile UTI attacks except one in this group occurred below the age of 12 months. A total of 10 patients in both healthy and non-healthy groups had postoperative hemorrhage after circumcision and only 1 patient had a wound infection. Conclusion: Concealed penis after circumcision does not lower perimeatal urethral and glanular sulcus uropathogenic bacterial colonization in healthy patients and does not protect unhealthy patients from febrile urinary tract infection attacks. If circumcision is planned, concealed penis should be avoided and also parents should be informed about the possible risks due to concealed penis before the procedure, particularly in patients with urinary tract abnormalities.